Telemedicine in Europe - Current Status and Future Perspectives - Ana-Maria CIOTI; Ana Maria Alexandra STANESCU; Ioana Veronica GRAJDEANU; Bogdan SERBAN; Elena POPESCU; Ovidiu Gabriel BRATU; Camelia Cristina DIACONU (Modern Medicine)
Telemedicine ensures remote medical services through technologies that facilitate the interaction between a health professional and patients and offers the possibility of a interdiciplinary consultation between specialists, in order to obtain a diagnosis and treatment plan. It involves secure transmission of medical data and information, through text, sound, images or other forms needed for the prevention, diagnosis, treatment and follow-up of patients. With the help of telemedicine, people from rural areas, with difi cult access to primary care, and those with reduced mobility can benefi t from healthcare services. This paper is a review of the latest data available in the literature regarding telemedicine and the future prespectives in this field in Europe.